1993
DOI: 10.1007/bf00279896
|View full text |Cite
|
Sign up to set email alerts
|

The GEF1 gene of Saccharomyces cerevisiae encodes an integral membrane protein; mutations in which have effects on respiration and iron-limited growth

Abstract: We have isolated a new class of respiration-defective, i.e petite, mutants of the yeast Saccharomyces cerevisiae. Mutations in the GEF1 gene cause cells to grow slowly on rich media containing carbon sources utilized by respiration. This phenotype is suppressed by adding high concentrations of iron to the growth medium. Gef1- mutants also fail to grow on a fermentable carbon source, glucose, when iron is reduced to low concentrations in the medium, suggesting that the GEF1 gene is required for efficient metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
97
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 44 publications
1
97
0
Order By: Relevance
“…Analysis of mutants unable to grow on low iron led to the discovery of the structural components of the high affinity iron transport system as well as genes required for copper transport (29), chloride transport (30), and vesicular traffic (8,31). These genes were identified through genetic screens in which mutagenized cells were selected for their inability to grow on either low iron (18), glycerol-ethanol media (30) or for the induction of iron-regulated genes (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of mutants unable to grow on low iron led to the discovery of the structural components of the high affinity iron transport system as well as genes required for copper transport (29), chloride transport (30), and vesicular traffic (8,31). These genes were identified through genetic screens in which mutagenized cells were selected for their inability to grow on either low iron (18), glycerol-ethanol media (30) or for the induction of iron-regulated genes (32).…”
Section: Discussionmentioning
confidence: 99%
“…These genes were identified through genetic screens in which mutagenized cells were selected for their inability to grow on either low iron (18), glycerol-ethanol media (30) or for the induction of iron-regulated genes (32). We have extended these studies using a genome-wide analysis of a homozygous diploid deletion collection.…”
Section: Discussionmentioning
confidence: 99%
“…The functional complementation by AtClC-c and -d (12, 32) of growth phenotypes of a yeast strain deleted for the single yeast CLC Gef1 (33) suggested that these plant CLC proteins function in anion transport but could not reveal details of their biophysical properties. We report here the first functional expression of a plant CLC in animal cells.…”
Section: /Hmentioning
confidence: 99%
“…A more definitive assignment of their physiological roles, however, is not yet possible. In this respect, it is interesting to note that only AtClC-c and AtClC-d were reported to complement (12,32) growth phenotypes of a Saccharomyces cerevisiae strain deleted for the single yeast CLC (ScClC or Gef) (33). Whether this is related to the fact that AtClC-c and -d, just like ScClC, carry serine in their signature sequence and hence probably prefer chloride over nitrate remains unclear.…”
Section: /Hmentioning
confidence: 99%
“…The expression cloning of the voltage-gated chloride channel C1C-0 from the electric organ of the marine ray Torpedo marmorata [1] led to the subsequent discovery of a large gene family of related proteins [2], which even includes members from Saccharomyces cerevisiae [3] and Escherichia coli [4]. In a single mammalian species, seven different C1C genes have been described so far [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%